Solving io ODEs with Laplace
Laplace transforms provide a convenient method for solving input-output (io) ordinary differential equations (ODEs).
Consider a dynamic system described by the io ODE—with \(t\) time, \(y\) the output, \(u\) the input, constant coefficients \(a_i,b_j\), order \(n\), and \(m \le n\) for \(n\in\mathbb{N}_0\)—as: \[\begin{aligned} {8} \label{eq:lap:ioode} \frac{\diff^n y} {\diff t^n} & {}+{} & a_{n-1} \frac{\diff^{n-1} y}{\diff t^{n-1}} & {}+{} & \cdots & {}+{} & a_1 \frac{\diff y} {\diff t} & {}+{} && a_0 y =\nonumber \\ b_m \frac{\diff^m u} {\diff t^m} & {}+{} & b_{m-1} \frac{\diff^{m-1} u}{\diff t^{m-1}} & {}+{} & \cdots & {}+{} & b_1 \frac{\diff u} {\diff t} & {}+{} && b_0 u. \end{aligned}\] Re-written in summation form, \[\begin{aligned} \label{eq:lap:ioode2} \sum_{i=0}^n a_i y^{(i)}(t) &= \sum_{j=0}^m b_j u^{(j)}(t), \end{aligned}\] where we use Lagrange’s notation for derivatives, and where, by convention, \(a_n = 1\).
The Laplace transform \(\mathcal{L}\) of yields $$\begin{align}\label{eq:lap:ioode3} \mathcal{L}\sum_{i=0}^n a_i y^{(i)}(t) &= \mathcal{L}\sum_{j=0}^m b_j u^{(j)}(t) \quad\Rightarrow \\ \sum_{i=0}^n a_i \mathcal{L} \left(y^{(i)}(t) \right) &= \sum_{j=0}^m b_j \mathcal{L} \left(u^{(j)}(t)\right). \tag{linearity} \end{align}$$ In the next move, we recursively apply the differentiation property to yield the following \[\begin{aligned} \label{eq:lap:ioode4} \sum_{i=0}^n a_i \left( s^i Y(s) + \underbrace{\sum_{k=1}^i s^{i-k} y^{(k-1)}(0)}_{I_i(s)} \right) &= \sum_{j=0}^m b_j s^j U(s), \end{aligned}\] where terms in \(I_i(s)\) arise from the initial conditions. Splitting the left outer sum and solving for \(Y(s)\), $$\begin{align}\label{eq:lap:ioode5} \sum_{i=0}^n a_i s^i Y(s) &+ \sum_{i=0}^n a_i I_i(s) = \sum_{j=0}^m b_j s^j U(s) \quad\Rightarrow \\ \sum_{i=0}^n a_i s^i Y(s) &= \sum_{j=0}^m b_j s^j U(s) - \sum_{i=0}^n a_i I_i(s) \quad\Rightarrow \\ Y(s) \sum_{i=0}^n a_i s^i &= U(s) \sum_{j=0}^m b_j s^j - \sum_{i=0}^n a_i I_i(s) \quad\Rightarrow \\ Y(s) &= \underbrace{\frac{\sum_{j=0}^m b_j s^j}{\sum_{i=0}^n a_i s^i} U(s)}_{Y_\text{fo}(s)} + \underbrace{\frac{-\sum_{i=0}^n a_i I_i(s)}{\sum_{i=0}^n a_i s^i}}_{Y_\text{fr}(s)}. \label{eq:laplace_io_ode_sol1} \end{align}$$
So we have derived the Laplace transform image \(Y(s)\) in terms of the forced and free responses (still in the \(s\)-domain, of course)! For a solution in the time-domain, we must inverse Laplace transform: \[\begin{aligned} \label{eq:laplace_io_ode_sol2} y(t) &= \underbrace{(\mathcal{L}^{-1}Y_\text{fo})(t)}_{y_\text{fo}(t)} + \underbrace{(\mathcal{L}^{-1}Y_\text{fr})(t)}_{y_\text{fr}(t)}. \end{aligned}\] This is an important result!
Consider a system with step input u(t) = 7us(t), output y(t), and io ODE $$\begin{aligned} \label{eq:laplace_io_ode_exa} \ddot{y} + 2 \dot{y} + y &= 2 u. \end{aligned}$$ Solve for the forced response yfo(t) with Laplace transforms.
From , $$\begin{align} y_\text{fo}(t) &= (\mathcal{L}^{-1}Y_\text{fo})(t) \\ &= \mathcal{L}^{-1}\left(\frac{\sum_{j=0}^m b_j s^j}{\sum_{i=0}^n a_i s^i} U(s)\right) \tag{\cref{eq:laplace_io_ode_sol1}} \\ &= \mathcal{L}^{-1}\left(\frac{2} {s^2 + 2 s + 1} U(s)\right). \tag{\cref{eq:laplace_io_ode_exa}} \end{align}$$ We can u(t) for U(s): $$\begin{aligned} U(s) &= (\mathcal{L}u)(s) \\ &= 7 (\mathcal{L}u_s)(s) \\ &= \frac{7} {s}, \end{aligned}$$ where the last equality follows from a transform easily found in .
Returning to the time response , $$\begin{aligned} y_\text{fo}(t) &= \mathcal{L}^{-1}\left(\frac{2} {s^2 + 2 s + 1} U(s) \right) \\ &= \mathcal{L}^{-1}\left(\frac{2} {s^2 + 2 s + 1} \cdot \frac{7} {s}\right). \end{aligned}$$
Substituting this into our solution, $$\begin{align} y_\text{fo}(t) &= 14 \mathcal{L}^{-1}\left( \frac{1} {s} - \frac{1} {(s+1)^2} - \frac{1} {s+1} \right) \tag{linearity} \\ &= 14 \left( \mathcal{L}^{-1} \frac{1} {s} - \mathcal{L}^{-1} \frac{1} {(s+1)^2} - \mathcal{L}^{-1} \frac{1} {s+1} \right) \\ &= 14 \left( u_s(t) - t e^{-t} - e^{-t} \right) \tag{\cref{tab:laplace_transforms}} \\ &= 14 \left( u_s(t) - (t + 1) e^{-t} \right). \end{align}$$ So the forced response starts at 0 and decays to a steady 14.
Online Resources for Section 10.5
No online resources.